Projection of macroeconomic indicators in SME sector by 2025 - Stevanović Mirjana; Nikolić Branislav (Trendovi u Poslovanju)
The paper is based on an analysis of companies and entrepreneurs who have made business (performed their activity) in the period of 2010-2014. We also analyzed the number of entrepreneurs, micro, small and medium enterprises, number of employees, gross social value, exports, imports, number of importers and exporters. The aim of the paper is the projection of macroeconomic indicators by 2025 in the Republic of Serbia, with emphasis put onto improvement of business conditions with the aim of Serbian economy growth. The result of the research should show that the macroeconomic projections in the SME sector are on the path of recovery and growth, but they are conditional on the quality of fiscal policy, reforms implementation pace, financial incentives, and creating an environment whose ultimate goal would be strengthening of the private sector and creating even favorable business conditions.